When primary hyperparathyroidism comes as good news. (4th June 2020) - Gallo, Daniela; Rosetti, Sara; Marcon, Ilaria; Armiraglio, Elisabetta; Parafioriti, Antonina; Pinotti, Graziella; Perrucchini, Giuseppe; Patera, Bohdan; Gentile, Linda; Tanda, Maria Laura; Bartalena, Luigi; Piantanida, Eliana
Abstract : Summary: Brown tumors are osteoclastic, benign lesions characterized by fibrotic stroma, intense vascularization and multinucleated giant cells. They are the terminal expression of the bone remodelling process occurring in advanced hyperparathyroidism. Nowadays, due to earlier diagnosis, primary hyperparathyroidism keeps few of the classical manifestations and brown tumors are definitely unexpected. Thus, it may happen that they are misdiagnosed as primary or metastatic bone cancer. Besides bone imaging, endocrine evaluation including measurement of serum parathyroid hormone and calcium (Ca) levels supports the pathologist to address the diagnosis. Herein, a case of multiple large brown tumors misdiagnosed as a non-treatable osteosarcoma is described, with special regards to diagnostic work-up. After selective parathyroidectomy, treatment with denosumab was initiated and a regular follow-up was established. The central role of multidisciplinary approach involving pathologist, endocrinologist and oncologist in the diagnostic and therapeutic work-up is reported. In our opinion, the discussion of this case would be functional especially for clinicians and pathologists not used to the differential diagnosis in uncommon bone disorders. Learning points: Brown tumors develop during the remodelling process of bone in advanced and long-lasting primary or secondary hyperparathyroidism. Although rare, they should be considered during the challenging diagnostic work-up of giant cell lesions. Coexistence of high parathyroid hormone levels and hypercalcemia in primary hyperparathyroidism is crucial for the diagnosis. A detailed imaging study includes bone X-ray, bone scintiscan and total body CT; to rule out bone malignancy, evaluation of bone lesion biopsy should include immunostaining for neoplastic markers as H3G34W and Ki67 index. If primary hyperparathyroidism is confirmed, selective parathyroidectomy is the first-line treatment. In advanced bone disease, treatment with denosumab should be considered, ensuring a strict control of Ca levels.